English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve equation for x Find any restrictions.

bx - cx = -c

2007-08-27 14:53:55 · 4 answers · asked by brighton 3 in Science & Mathematics Mathematics

4 answers

bx - cx = -c
(b - c)x = -c
x = -c/(b-c)
restriction: b-c cannot be 0.

2007-08-27 14:59:49 · answer #1 · answered by Philo 7 · 0 0

bx - cx = -c
grouping similar terms:
x(b-c) = -c
x = -c/b-c -- equation for x
b cannot be = to c

2007-08-27 22:01:24 · answer #2 · answered by toffer 3 · 0 0

bx - cx = -c

x (b - c) = -c

x = -c / ( b-c )

this function is undefined when b = c

2007-08-27 22:02:07 · answer #3 · answered by Will 4 · 0 0

x (b-c) = -c
x = -c/(b-c)

the restriction is that b cannot equal c!!

2007-08-27 22:00:15 · answer #4 · answered by theanswerman 3 · 0 0

fedest.com, questions and answers